Lactation Massage and Hypnobreastfeeding Relaxation Techniques in Breastfeeding Mothers - Sunarti, Nina; Lutfiyanti , Aulia (LPPM STIKes Muhammadiyah Ciamis, 2024)
Breast milk is a kind of food that is good for meeting all the physical needs of babies. Breast milk contains most of the nutritional elements, hormones and immunity of a baby. After that the baby will only get breast milk until the baby is six months old, after the baby is six months old the baby will be given complementary food for breast milk until the baby is even two years old. Purpose: this research is to find out the description of nursing care for normal postpartum mothers who experience ineffective breastfeeding at Koja Jakarta Hospital in 2023 with lactation massage and hypnobreastfeeding relaxation techniques. Methodology: the research used is a descriptive researcher with a case study design that will be carried out in June 2023. Results: a study of patients who experienced ineffective breastfeeding by means of lactation massage and hypnobreastfeeding relaxation techniques, could increase milk production, reduce breast swelling and reduce pain. This can happen because of the willingness of the client to follow. Conclusion: lactation massage techniques and hypnobreastfeeding relaxation techniques can be done when complaints of a little milk coming out, anxiety, swelling in the breasts of post partum mothers are normal.